Nilai-nilai Pendidikan dalam Novel Mitra Sejati Karya Tulus Setiyadi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
This study aims to describe the intrinsic elements in the novel Mitra Sejati by Tulus Setiyadi and the educational values ​​in the novel Mitra Sejati by Tulus Setiyadi. This type of descriptive qualitative research. The data sources for the novel Mitra Sejati by Tulus Setiyadi and the data for this study are quotes that contain intrinsic elements and educational values. Data collection techniques used library techniques and note-taking techniques. The instrument used by the researcher himself was the main instrument. The validity of the data used triangulation of sources, researchers, and theories. The analysis of this research uses an interactive analysis model. The technique of presenting the results of the analysis used the informal presentation method. The results found (1) intrinsic elements include: (a) the theme of the novel Mitra Sejati is friendship and the struggle of two children in continuing their education (b) The characters and characterizations consist of the main characters, namely Arga and Bayu, the additional characters are Pak Karyo, Ratih, Mbok Suminah, Mas Guntur, Mbah Kromo, Budhe Tumi, Indri, Nuning, Raras (c) The plot used is a forward plot (d) The setting consists of place setting, time setting, and socio-cultural setting (e) The point of view used is the point of view the third person's point of view is omniscient. (2) educational values ​​consist of: (a) the value of religious education includes 2 (two) aspects (b) the value of moral education includes 2 (two) aspects and (c) the value of cultural education includes 2 (two) aspects. In this study, it was concluded that the researcher only examined the intrinsic elements and educational values ​​of the Mitra Sejati novel by Tulus Setiyadi.